2024
DOI: 10.1007/s11235-024-01104-x
|View full text |Cite
|
Sign up to set email alerts
|

Digital product passports as enablers of digital circular economy: a framework based on technological perspective

Konstantinos Voulgaridis,
Thomas Lagkas,
Constantinos Marios Angelopoulos
et al.

Abstract: Taking into consideration the existing Industry 4.0 infrastructures and the rise of Industry 5.0 (I5.0), more and more solutions are being developed, aiming towards increased environmental consciousness through advanced technologies, and human centricity. However, there are ongoing requirements on data traceability, and access to the related actors, to ensure the establishment of sustainable solutions, within the context of a digital circular economy (DCE) environment. Digital product passports (DPPs) constitu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 62 publications
0
2
0
Order By: Relevance
“…Essential components for a well-functioning DPP are the ways of data exploitation (tagging of products), the choice of database used, efficient ways of data curation (data denoising and data cleaning), data sharing concepts, and finally the leverage of all collected data [16]. Plociennik et al [17] identified information requirements, collaboration along the value chain, product identification, and fulfillment of legal obligations as the main requirements for establishing a DPP.…”
Section: Digital Product Passportmentioning
confidence: 99%
See 1 more Smart Citation
“…Essential components for a well-functioning DPP are the ways of data exploitation (tagging of products), the choice of database used, efficient ways of data curation (data denoising and data cleaning), data sharing concepts, and finally the leverage of all collected data [16]. Plociennik et al [17] identified information requirements, collaboration along the value chain, product identification, and fulfillment of legal obligations as the main requirements for establishing a DPP.…”
Section: Digital Product Passportmentioning
confidence: 99%
“…Voulgaridis et al [16] propose a cloud-based digital passport version consisting of a two-layer structure, Passport Generation and Digital Passport, which allows the separation of business-sensitive and consumer-relevant data. In the Passport Generation phase, all production data from different business partners are provided and collected separately in a closed system to increase data security and trustworthiness.…”
Section: Digital Product Passportmentioning
confidence: 99%